Predictability of stock returns of financial companies and the role of investor sentiment: A multi-country analysis - Kadilli, Anjeza (Journal of Financial Stability, 2015)
We investigate the role of investor sentiment in predicting annual stock returns of financial companies at the aggregate level and for a large panel of developed countries within two panel regime-switching models, with threshold and with smooth transition between regimes. We find a negative, but insignificant effect of sentiment on future returns during normal times, and a surprisingly positive and strongly significant effect during crisis times. This result could be explained by a differentiated impact of investor sentiment on specific types of stocks, as opposed to a wide horizon of stocks. We find less evidence of predictability for shorter-term financial stock returns. To the best of our knowledge, this study is the first to examine the predictability of financial stock returns within a panel regime-switching framework.